The Comparison of Different Mathematical Methods to Determine the BOD Parameters, a New Developed Method and Impacts of These Parameters Variations on the Design of WWTPs - Şibil, Rahim; Berkün, Mehmet; Bekiroğlu, Serkan (Elsevier Science Inc, 360 Park Ave South, New York, Ny 10010-1710 Usa, 2014)
One of the most common tests for the determination of strength and organic content of wastewater is the biochemical oxygen demand (BOO). This test is widely applied to define organic water pollution and to control the performance of wastewater treatment plants. Generally, BOD is standardized by the measurement of oxygen consumption in 5 days (BOD5). But, determination of the ultimate biochemical oxygen demand (BODu), which is taken 28 days and the reaction rate constant (k) are necessary to understand the organic strength of the wastewater. In this study, the different mathematical methods in order to determine the BOO parameters (BODu, k) and two different BOO test method (respirometer and dilution method) are investigated comparatively. Also, a new method based on cubic spline method to estimate ultimate BOD values is developed. Moreover, the impacts of BOD parameters on the design of an activated sludge and aerated lagoon systems are analyzed by using a written user-friend program, which is developed for designing WWTPs by the mean of C++ programming language. Analytical results show that there is a satisfactory linear relationship between respirometric and dilution BOO values. Also, the mathematical methods, including new developed method generally provide consistent results with high correlation coefficients. On the other hand, it is found that LOG differences method for respirometric test and the new developed method for dilution test do not give good correlation coefficients. Moreover, activated sludge and aerated lagoons systems' sizes show significant changing depending on the variations of the BOD parameters. Consequently, BOD parameters show significant changes depending on the different test and mathematical methods. Therefore, the changing of these parameters impact a lot of situation such as ultimate BOD estimation, the wastewater treatment plants design, the dimensions of the plants and cost of the plants. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: BOD; Mathematical Modeling; Wastewater; Activated Sludge; Aerated Lagoon; C Plus Programming